2021
DOI: 10.1186/s12883-021-02315-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative monitoring of visual evoked potentials in patients undergoing transsphenoidal surgery for pituitary adenoma: a systematic review

Abstract: Background Transsphenoidal surgery is the gold standard for pituitary adenoma resection. Although rare, a serious complication of surgery is worsened vision post-operatively. Objective To determine whether, in patients undergoing transsphenoidal surgery for pituitary adenoma, intraoperative monitoring of visual evoked potentials (VEP) is a safe, reproducible, and effective technological adjunct in predicting postoperative visual function. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous studies have sought a better means for intraoperative prediction of postoperative visual function, but examinations of tools such as visual evoked potentials are limited and inconclusive. 13,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have sought a better means for intraoperative prediction of postoperative visual function, but examinations of tools such as visual evoked potentials are limited and inconclusive. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has attempted to use intraoperative visual evoked potentials to assess optic function in real-time, but the results have remained inconclusive. 13,14 An intraoperative tool predicting the risk of postsurgical visual loss would aid in postoperative care and management because patients at risk for visual deficit can be monitored in the intensive care unit (ICU) and appropriately treated with vasopressors and corticosteroids.…”
mentioning
confidence: 99%
“…To date, many clinical studies have explored and confirmed a good correlation between intraoperative VEP and post-operative visual function, but most of them are limited to the relationship between VEP amplitude changes and visual function (16)(17)(18)(19)(20), and VEP is reliable in predicting new visual damage at 50% alarm criteria (16,20). Previous studies have paid less attention to P100 latency in VEP, and none of them could summarize the threshold for the degree of P100 latency in VEP prolongation (21). In the present work, data from 180 eyes in 90 patients were analyzed, and 8.61% was determined as the threshold for the degree of P100 prolongation for predicting post-operative visual deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Visual evoked potential (VEP) is an established modality that allows safe brain tumor resection and visual acuity preservation during surgery [1][2][3][4]. Additionally, VEP is essential in preserving visual function during endoscopic transsphenoidal surgery (ETS) for sellar and parasellar tumors located near the optic pathway [5,6].…”
Section: Introductionmentioning
confidence: 99%